Learning Technology from the Perspective of Progressivism Philosophy - Bustanur; Irfandi; Alhairi; Kiprah Piawi (al-Afkar, Journal For Islamic Studies, 2025)
Technology that is developing very rapidly is also felt in the world of education, which is called learning technology. The birth of learning technology is in line with the progressivism philosophy that education must always change with the times. This research aims to analyze learning technology from the perspective of progressivism philosophy. The research method used uses qualitative methods. From the results of the analysis, it was found that the philosophy of progressivism and learning technology are similar in terms of the direction of development and change in education. Learning technology is a product of progressivism philosophy. This is because the philosophy of progressivism holds that education must adapt dynamically to the progress of the times, while learning technology is the world of education's response to these changes. In general, learning technology based on the philosophy of progressivism was found to have a lot of suitability both in terms of curriculum, learning process, and users, namely students and teachers.